Human morphology and hydrodynamics - Clarys, J. P. (Swimming III. Proceedings of the Third International Symposium of Biomechanics in Swimming, University of Alberta, Edmonton, Canada, 1979)
The propulsion of a body in a liquid requires energy, which must either be provided by an outside towing force or be developed by an inside propulsive force. In the simplest case, i.e., a uniform movement in the horizontal plane, neither the potential energy nor the kinetic energy of the body changes, so all energy being developed must be absorbed by the liquid. Therefore, the kinetic energy of the liquid particles should increase. The force (per unit of time) corresponding to this change in quantity of movement (change in impulse) of liquid mass is the drag that the body encounters in the liquid and that must be overcome by the towing ship or propulsive force. However, the human body, like the shape of a ship, presents an additional difficulty, in the sense that it moves in the boundary plane between two media: water and air, whereby changes in flow also cause changes in the level of the boundary plane (waves). In other words, the problems are much more complex than those of a body moving in a single medium. If one adds to these problems the uneven and poorly streamlined shape of the human body plus its possibility for "self-propulsion," the problems seem endless. One purpose of this study was to clarify some of these points through systematic and fundamental investigations.